SOCIAL MEDIA IN ELECTIONS: EVIDENCE FROM THE UNITED STATES, GERMANY, AND AUSTRALIA - Bruns, Axel; Stromer-Galley, Jennifer; Karia, Jill; Münch, Felix Victor; Kessling, Philipp; Ohme, Jakob; Pfiffner, Nico; Friemel, Thomas N.; Vilkins, Samantha; Fitzgerald, Katherine; Choucair, Tariq; Angus, Daniel; et al. (AoIR Selected Papers of Internet Research, 2026)
The year 2024 was marked by an unprecedented confluence of elections around the world, with more than 50% of the world’s population called upon to vote on the future of their governments; perhaps most important of these was the presidential election in the United States in November 2024, which saw Donald Trump returned to the Presidency – an outcome whose immense consequences are already being felt strongly around the world, mere months into the new administration’s term.In particular, Trump’s victory and his immediate upending of the rule of law at home and world order abroad impacts directly on major subsequent elections elsewhere in the world, including in closely allied nations like Germany (whose federal election took place in February 2025) and Australia (where a federal election is scheduled for April or May 2025). The resurgence of Trumpism emboldened extreme right parties like Germany’s Alternative für Deutschland (AfD), which attracted over 20% of the popular vote in the 2025 election; and Trump’s threats of import tariffs and wavering support for international alliances are emerging as a key topic in the 2025 Australian election campaign.These developments are further exacerbated by substantial changes in online campaigning environments and strategies. Social media platform operators like Mark Zuckerberg and Elon Musk have closely aligned themselves with the Trump administration (or in Musk’s case, joined it outright), in part to seek protection against European Union and other regulations that require action against disinformation, abuse, and hate speech, and enforce transparency and researcher data access; they have dismantled their content moderation and fact-checking teams; and (in Musk’s case) are actively disseminating disinformation, hate speech, and extremist content. This has also opened the door for other political agitators and influence operators to push problematic materials, including conspiracy theories and AI-generated disinformation.Finally, the changing platform landscape – marked by the gradual decline of Facebook, a steady exodus from X under Musk’s leadership, the rapid rise of TikTok, and the emergence of federated Twitter alternatives like Mastodon and Bluesky – also necessitates substantial changes in electoral campaigning on the one hand, and in campaign research methods on the other. This panel brings together five papers from major research teams that trace these developments through the US, German, and Australian elections of 2024 and 2025. They provide new insights into the changing electoral campaigning environments of the present moment, and offer new approaches for how we can conduct such research under these changed circumstances.Paper 1 addresses the 2024 US presidential election, and explores in particular how the digital advertising funded by Elon Musk engaged in targeted disinformation of key voter groups. Scraping data from the Meta Ad Library and Google Ad Transparency Center, it documents substantial efforts to pollute the information environment with such content.Paper 2 shifts our attention to the 2025 German election. It explores the strategies of political campaigners for embracing TikTok, and especially the interlinkage between political talk show appearances and the talking points presented in campaign videos on TikTok – a platform which serves both to trial such talking points for use in talk shows, and to redistribute television clips of talk show appearances afterwards.Paper 3 continues our focus on the role of TikTok in the German election, but shifts the emphasis to the experience of ordinary users. Drawing on more than 300 data donations from German TikTok users, it examines their exposure to political content on the platform, explores the role of TikTok’s algorithms in pushing users towards specific videos, and investigates whether such algorithmic amplification is asymmetrical across parties.Paper 4 extends a long tradition of research into the use of social media in Australian elections. Traditionally, Twitter and Facebook served as key campaigning spaces, but this has diversified considerably now, and the paper therefore presents an ambitious cross-platform data gathering and analysis agenda for the 2025 election. It also employs the novel practice mapping technique to examine campaigning patterns in the election.Paper 5 concludes the panel. Building on concepts from semiotic theory, it combines topic modelling, named entity recognition, part-of-speech tagging, and dependency parsing methods to systematically identify the discursive and semionarrative structures of Facebook posts by and comments to the leading candidates in the 2022 and 2025 Australian elections, exploring differences between candidates and changes over time.In combination, then, these five papers examine election campaigning on social media across three major national elections, drawing on innovative conceptual frameworks and methodological approaches and applying them to a wide range of platforms and practices. They offer critical new insights into the state of social media campaigning, and important impulses for future research agendas in a rapidly changing world.Individual extended abstracts for these five papers are included in the PDF submission.